MANAJEMEN KINERJA APARATUR SIPIL NEGARA PADA KANTOR KECAMATAN MALUNDA KABUPATEN MAJENE - Sjuaib Hannan (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
The Head of Subdistrict as Top Management is expected to be able to regulate and motivate the apparatus to be able to work optimally both in administrative and development matters in Malunda District. Good apparatus management is expected to achieve a goal, namely improving work performance in answering challenges progress of the times so that the government can provide excellent service to the community. But there is no doubt that in reaching the target, there are many factors that can influence it, such as work motivation, employee resources and employee welfare. In the opinion of the authors, these three factors are able to improve performance and good performance so that a good government governance system is realized.